2020
DOI: 10.3389/fmicb.2020.02014
|View full text |Cite
|
Sign up to set email alerts
|

The Strengths of Scanning Electron Microscopy in Deciphering SARS-CoV-2 Infectious Cycle

Abstract: Electron microscopy is a powerful tool in the field of microbiology. It has played a key role in the rapid diagnosis of viruses in patient samples and has contributed significantly to the clarification of virus structure and function, helping to guide the public health response to emerging viral infections. In the present study, we used scanning electron microscopy (SEM) to study the infectious cycle of SARS-CoV-2 in Vero E6 cells and we controlled some key findings by classical transmission electronic microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 30 publications
13
68
0
3
Order By: Relevance
“…The cells were subsequently infected with SARS-CoV-2 (100 TCID50) and cultured at 37°C for 48hrs. Also, the supernatant was collected every 12, 16, 24, 36, and 48hrs (3 wells per each time) [70] for qPCR. We extend the observation till 48hrs to assess the extracts efficacy after 36hrs post-infection.…”
Section: Pre-treatment Of Cells Prior To Virus Infection (Anti-viral mentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were subsequently infected with SARS-CoV-2 (100 TCID50) and cultured at 37°C for 48hrs. Also, the supernatant was collected every 12, 16, 24, 36, and 48hrs (3 wells per each time) [70] for qPCR. We extend the observation till 48hrs to assess the extracts efficacy after 36hrs post-infection.…”
Section: Pre-treatment Of Cells Prior To Virus Infection (Anti-viral mentioning
confidence: 99%
“…The three extract-treated SARS-CoV-2 were subsequently used to infect Vero E6 cells at 37°C for 48hrs. As described above, the relative mRNA expression levels of SARS CoV-2 RdRP gene, viral load, and the level of virus neutralization were assessed with qRT-PCR [62] of every 12,16,24,36, and 48hrs supernatants cell samples [70]. During the post infection cycle, the plates were analyzed by observing virus-induced CPE by light microscope (Nikon-ECLIPSE-Ti), and plaque formation was determined by crystal violet staining (C0775; Sigma-Aldrich), as previously described [47].…”
Section: Pre-treatment Of Virus Prior To Infection (Virucidal Activity)mentioning
confidence: 99%
“…The other parameters were obtained from the literature. 21 , 23 , 24 , 35 , 36 The roughness of the sensing chips (0.3 nm; measured by AFM) was neglected in the above calculation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, active targeting (through the attachment of targeting ligands such as specific antibodies, aptamers and vitamins) has been the highlight and focus in the design of targeted drug delivery systems. In the case of COVID-19, the structure of SARS-CoV-2 virus allowed for the specific targeting of lung cells through ACE2 receptors and cellular uptake via clathrin-mediated endocytosis (Brahim Belhaouari et al, 2020). The Spike (S) protein on the SARS-CoV-2 virus, in particular, derives the entry of the virus into cells with the S1 surface unit targeting ACE2 receptors (Figure 2).…”
Section: Cellular Entry and Uptake Of Sars-cov-2 Virusmentioning
confidence: 99%
“…Cellular kinetics will help in the design of site-specific nanoparticles as well as punctual nanomedicines that can deliver the therapeutic cargo in a timely fashion within cells. Belhaouari et al observed the infectious cycle of SARS-CoV2 using scanning electron microscopy and found that its virions were located at the cell surface early post-infection (Brahim Belhaouari et al, 2020) and that the virus corona spikes were sandwiched between the particles and the cellular membrane. As most spherical nanoparticles that are taken up inside the cell via endocytosis, the virus then escapes the endosome and the single-stranded RNA is released within the cytoplasm where replication and transcription take place through the replication/transcription complex (RTC) (Boopathi et al, 2020).…”
Section: Trafficking Of Sars-cov2 Within Cellsmentioning
confidence: 99%